Termination of translation in bacteria may be modulated via specific interaction between peptide chain release factor 2 and the last peptidyl-tRNA(Ser/Phe). - Arkov, A L (1993)
The 5' context of 671 Escherichia coli stop codons UGA and UAA has been compared with the context of stop-like codons (UAC, UAU and CAA for UAA; UGG, UGC, UGU and CGA for UGA). We have observed highly significant deviations from the expected nucleotide distribution: adenine is over-represented whereas pyrimidines are under-represented in position -2 upstream from UAA. Uridine is over-represented in position -3 upstream from UGA. Lysine codons are preferable immediately prior to UAA. A complete set of codons for serine and the phenylalanine UUC codon are preferable immediately 5' to UGA. This non-random codon distribution before stop codons could be considered as a molecular device for modulation of translation termination. We have found that certain fragment of E. coli release factor 2 (RF2) (amino acids 93-114) is similar to the amino acid sequences of seryl-tRNA synthetase (positions 10-19 and 80-93) and of beta (small) subunit (positions 72-94) of phenylalanyl-tRNA synthetase from E. coli. Three-dimensional structure of E. coli seryl-tRNA synthetase is known [1]: Its N-terminus represents an antiparallel alpha-helical coiled-coil domain and contains a region homologous to RF2. On the basis of the above-mentioned results we assume that a specific interaction between RF2 and the last peptidyl-tRNA(Ser/Phe) occurs during polypeptide chain termination in prokaryotic ribosomes.